Seleção entre e dentro de progenies de acácia-negra (Acacia mearnsii De Wild.) - Gazzana, Denise (2023)
Black wattle is mainly cultivated in the Rio Grande do Sul State of Brazil. The black wattle bark is a raw material for tannin and the wood part for cellulose, paper and energy industry. Black wattle cultivation is important for soil conservation, as erosion mitigation, nitrogen supply, and soil structuration and moisture preservation, being essentially important for small farms. Commercial scale production of black wattle demands for the development of clonal propagation techniques, because of it results in uniform populations with high productivity. In this context, this study aimed to evaluate black wattle progenies and to develop selection strategies of genotypes for rooting competence of mini-cuttings and clones for vegetative multiplication rate. For genotype and clone selection, single-bud mini-cuttings were treated with indole butyric acid at a concentration of 2,000 mg L-1 . The Mini-cuttings were evaluated for survival and rooting percentages, number and average length of the three largest roots, and number of rooted mini-cuttings per mini-stump at 30 days of cultivation. The identification of the best genotypes and clones was carried out using the Selegen REML/BLUP software. Genotype selection within progenies can be performed for the number of rooted mini-cuttings, enabling to select genotypes with high adventitious rooting competence and maintaining genetic variability for new selection cycles. The selection of clones was done based on the percentage of rooting and the number of rooted mini-cuttings per mini-stump, taking into account the genotypic effects with the greatest direct and indirect gains of selection and the stability and adaptability. This breeding strategy gives the possibility of selecting genotypes within progenies and clones of black wattle competent for asexual propagation by minicuttings.